Contribuições à análise dos impactos da microgeração distribuída por fonte fotovoltaica nos sistemas de distribuição de energia elétrica - Almeida, Lucas Rodrigues de (2024)
The growth of photovoltaic distributed generation has introduced significant challenges to both the operation and planning of power distribution systems. Currently, operational problems, power quality issues, and protection concerns are very common, directly associated with the high penetration of solar photovoltaic generation systems. Among the most commonly faced problems are voltage violations, exceeding thermal limits of transformers and conductors, increased voltage unbalances and harmonic distortions, as well as high technical losses and improper operation of overcurrent protection systems. In this context, this work aims to present contributions to the analysis of the impacts of photovoltaic distributed generation on power distribution systems through: (a) characterization, through experimental tests, of inverters used in photovoltaic distributed generation, in terms of harmonic and inter-harmonic emissivity, injection of direct current, and short-circuit contribution, since such information is rarely found in manufacturer catalogs; (b) development and construction of a voltage sag generator for conducting short-circuit contribution tests of the tested inverters; (c) development of a methodology for analyzing the hosting capacity of photovoltaic distributed generation considering a stochastic allocation approach in low-voltage circuits involving the most frequently encountered impacts in the distribution system, as well as the application of traditionally adopted mitigation methods; (d) development of a computational tool with a graphical interface for processing hosting capacity analyses; (e) development of a methodology for studying the impact of photovoltaic distributed generation on the protection of power distribution systems, considering a time-domain approach. As a result, important solutions and discussions are presented to assist engineers in better planning and management of photovoltaic distributed generation, contributing to the sustainability and efficiency of distribution networks in the face of the growing use of photovoltaic solar energy.